Sequential solid-phase fabrication of bifunctional anchors on gold nanoparticles for controllable and scalable nanoscale structure assembly - Kim, Jeong-Hwan (Langmuir : the ACS journal of surfaces and colloids, 2008)
This letter reports a serial solid-phase placement approach to synthesize anisotropically or symmetrically functionalized gold nanoparticles (AuNPs), in which the functionality and directionality (i.e., numbers, locations, and orientations) of the functional ligands are controlled. The solid-phase ligand exchange methodology using highly rigid filter papers enabled us to produce two types of bifunctionalized (bif-) AuNPs in a site-specific manner with increased yield and accuracy: (1) homobif-AuNPs with two carboxyl groups at approximately 180 degrees (para configuration) and (2) heterobif-AuNPs with one carboxyl and one amine functional groups at less than 180 degrees but greater than 90 degrees (meta configuration). Their chemical functionality was validated by 1H nuclear magnetic resonance as well as cyclic voltammetry after ferrocene ethylamine coupling reactions. The directional assemblies of 1D chains with homobif-AuNPs and 2D rings with heterobif-AuNPs were demonstrated through diamine and imidization coupling reactions, respectively, further validating their highly functional and directional selectivity, which is critical to realizing the practical nanoscale assembly